Optimizing Iiot Performance: Intelligent Selection of Sdn Controllers Through Ahp Analysis - Urrea-Onate, E; Benitez-Machado, D (Wiley-Hindawi, 2024)
This article deals with the use of software-defined networking (SDN) in the Industrial Internet of Things (IIoT). The use of SDN in IIoT can solve the limitations presented by traditional networks in order to guarantee quality of service (QoS) for new applications. The approach of this work centers on the selection of an SDN controller that satisfies the requirements for the networks of IIoT. Selection is based on the characteristics of the SDN controllers and employs the analytic hierarchy process (AHP). From the review conducted, and as a result of the work, the group of the current best SDN controllers for IIoT is identified, which is a part of the subsequent selection process. Another contribution of this study is that it defines the criteria for comparing these controllers and selecting the most suitable one for this type of application. The established criteria and the employed quantification method via AHP enrich the decision-making process, providing a replicable model for future selections. The objectives and criteria established can be useful for other SDN selection processes to be used in scenarios where delay, jitter, and packet loss are key parameters to consider. This nuanced approach, accommodating both theoretical frameworks and empirical observations, offers an advancement in the strategic deployment of SDN within IIoT environments. © 2024 Claudio Urrea and David Benítez.